EPISTAKSIS SEBAGAI KEGAWATDARURATAN TELINGA HIDUNG TENGGOROK: TINJAUAN KEPUSTAKAAN - Irwan Triansyah; Khuntum Khairatul Ummah; Yanti Fitri Yasa; Nadia Purnama Dewi; Ade Teti Vani (Nusantara Hasana Journal, 2026)
Epistaxis is one of the most common emergencies encountered in otorhinolaryngology–head and neck surgery (ORL-HNS) practice. Although most cases are mild, severe epistaxis, particularly of posterior origin, may lead to serious complications. This literature review aims to comprehensively discuss epistaxis, including its definition, epidemiology, etiology, pathophysiology, classification, and principles of management based on clinical guidelines. A narrative literature review method was applied by analyzing textbooks, clinical guidelines, and scientific journals related to epistaxis, including Logan Turner’s guidelines, the American Academy of Otolaryngology–Head and Neck Surgery (AAO-HNS) recommendations, and otorhinolaryngology consensus statements. Epistaxis is classified into anterior and posterior types based on the bleeding source, each with distinct pathophysiological mechanisms and clinical implications. Anterior epistaxis is commonly associated with local factors and generally responds well to conservative treatment, whereas posterior epistaxis is often related to systemic conditions and requires more aggressive interventions. Management should follow a stepwise approach in accordance with clinical guidelines. Epistaxis is an important ORL-HNS emergency that requires a systematic diagnostic and therapeutic approach. Understanding the pathophysiology and classification of epistaxis is essential for selecting effective and safe management strategies based on clinical guidelines, thereby reducing complications and recurrence